2015
DOI: 10.1055/s-0035-1554220
|View full text |Cite
|
Sign up to set email alerts
|

Does Intrawound Application of Vancomycin Influence Bone Healing in Spinal Surgery?

Abstract: Introduction Surgical site infections represent a major complication of spinal surgery. The application of lyophilized vancomycin into the wound is reported to significantly decrease infection rates. As concentrations applied locally can exceed the minimal bacterial inhibitory concentration for more than a 1000-fold, toxic side effects on local tissue may be possible. Materials and Methods Primary osteoblast cell cultures were generated from bone tissue samples of 10 patients. Samples were incubated in absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…Eder et al demonstrated the in vitro, negative, dose-dependent effect of local vancomycin powder on osteoblast activity. 5 Osteoblast cell cultures were exposed to 0, 3, 6, or 12 mg/cm 2 of vancomycin powder. At concentrations only above 3 mg/cm 2 , a decline in the pH with a concomitant decrease in osteoblast activity was noted.…”
Section: Dosage Effect On Complicationsmentioning
confidence: 99%
“…Eder et al demonstrated the in vitro, negative, dose-dependent effect of local vancomycin powder on osteoblast activity. 5 Osteoblast cell cultures were exposed to 0, 3, 6, or 12 mg/cm 2 of vancomycin powder. At concentrations only above 3 mg/cm 2 , a decline in the pH with a concomitant decrease in osteoblast activity was noted.…”
Section: Dosage Effect On Complicationsmentioning
confidence: 99%
“…DAD: dextrosa en agua destilada. Fuente: creación propia de seguridad in vivo e in vitro (65,(149)(150)(151)(152)(153) . De este modo, muchas decisiones se tomarán en relación con el riesgo y el beneficio para el paciente, en el contexto de un asunto que está en continuo desarrollo y en el que existen varios cuestionamientos que requieren mayor investigación para tomar decisiones clínicas basadas en la evidencia.…”
Section: Discussionunclassified
“…Furthermore, Eder et al [26] examined the toxic effect of different concentrations of vancomycin and showed that new bone formation was inhibited at high doses through the impairment of migration, proliferation, and differentiation of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%